1989
DOI: 10.1007/bf00456392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drug solubility in the vehicle on clinical efficacy of ointments

Abstract: In a bilateral paired comparison (randomized double-blind study) 31 dermatitis patients (atopic and contact dermatitis) were tested with two ointments containing 0.0056% betamethasone-17-benzoate. One ointment was applied on each side of the body. The topical formulations differed in their solution capacities for the drug by a factor of about 50 (solution-type: high mutual affinity between drug and vehicle; suspension-type: low affinity). The different antiinflammatory effects were studied visually by assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Based on these in vivo results, the determining factors for drug penetration into human skin could be identified. For validation of these data in clinical situations, a randomized double-blind study was performed with dermatitis patients [82]. The results of this study confirmed the assumption that the clinical efficiency of a suspension-type ointment is higher than a solution-type ointment for a given drug.…”
Section: Duesseldorf/hamburg (Germany): Bernhard Lippold and Claudia supporting
confidence: 64%
“…Based on these in vivo results, the determining factors for drug penetration into human skin could be identified. For validation of these data in clinical situations, a randomized double-blind study was performed with dermatitis patients [82]. The results of this study confirmed the assumption that the clinical efficiency of a suspension-type ointment is higher than a solution-type ointment for a given drug.…”
Section: Duesseldorf/hamburg (Germany): Bernhard Lippold and Claudia supporting
confidence: 64%
“…Bioequi valence may be established through a wellcontrolled clinical trial or even through mea surement of a pharmacological or pharmaco dynamic end point. For example, skin blanch ing caused by corticosteroids has long been used to establish a dose response relationship and assess bioequivalence [10][11][12] and is now sanctioned for such purposes. Establishing that the concentration of drug within the treated tissue correlates with clinical perfor mance or to some relevant pharmacological end point is another approach to bioequival ence which is currently being debated.…”
Section: Bioavailability and Bioequivalence O F Topical Productsmentioning
confidence: 99%
“…Gibson et al could not confirm significant differences in blanching activity of clobetasol after a tenfold dilution [19]. This finding can only be understood by assuming that a solution-type ointment was used as vehicle [51]. Furthermore, the results of Watson and Findlay revealing nearly identical liberation of clobetasol from a propylene glycol and a paraffin ointment can be interpreted insomuch that clobetasol was most likely suspended in the concentration used [84].…”
Section: Influence Of the Vehicle On The Effect Of Topical Corticostementioning
confidence: 84%
“…It is also possible that a dilution of the corticosteroid in certain ointment bases does not reduce its potency equivalently [19,51], and may as a consequence cause unexpected side effects. Gibson et al could not confirm significant differences in blanching activity of clobetasol after a tenfold dilution [19].…”
Section: Influence Of the Vehicle On The Effect Of Topical Corticostementioning
confidence: 95%
See 1 more Smart Citation